2002
DOI: 10.1034/j.1600-0676.2002.01622.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evidence for hepatic progenitor cells in liver diseases

Abstract: Background/Aim: Proliferative bile ductular reactions occur in a variety of liver diseases in humans. It is a matter of debate whether such reactions result from progenitor cell proliferation with biliary and hepatocytic differentiation, versus biliary metaplasia of damaged hepatocytes. We investigated bile ductular reactions in liver diseases, paying particular attention to the presence of cells with intermediate (hepatocytic/ biliary) features (oval-like cells). Methods: Five specimens each were selected of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
99
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(108 citation statements)
references
References 14 publications
(24 reference statements)
6
99
0
3
Order By: Relevance
“…[17][18][19][20] Oval cells are commonly found in pathological structures called "ductular reactions" (DRs). [21][22][23][24][25] Some investigators have suggested that oval cells in human liver disease should be referred to as "intermediate hepatobiliary cells" because they may not be equivalent to oval cells in rodents. 21 A common characteristic of these human diseases (also common with rodent experimental systems) is that regeneration of the resident hepatocyte population is severely limited.…”
mentioning
confidence: 99%
“…[17][18][19][20] Oval cells are commonly found in pathological structures called "ductular reactions" (DRs). [21][22][23][24][25] Some investigators have suggested that oval cells in human liver disease should be referred to as "intermediate hepatobiliary cells" because they may not be equivalent to oval cells in rodents. 21 A common characteristic of these human diseases (also common with rodent experimental systems) is that regeneration of the resident hepatocyte population is severely limited.…”
mentioning
confidence: 99%
“…28,29 The basic reaction types of the liver alterations can be divided into well-defined categories: adaptive changes, degeneration and intracellular storage, cell death (necrosis/ apoptosis), inflammation, fibrosis, and structural reorganization, as well as regeneration/proliferation (cirrhosis). 29 Apoptosis occurs in several liver diseases, with a striking form appearing to be the Councilman-like body seen in alcoholic but also in viral hepatitis. It may have role in the pathogenesis of cholestasis, biliary atresy, the ''vanishing bile duct syndrome,'' and alcoholic liver injury.…”
Section: Overview Of Liver Alterationsmentioning
confidence: 99%
“…The regenerating nodules and accompanying fibrosis interfere with blood flow through the liver and result in portal hypertension, hepatic insufficiency, jaundice, and ascites. [28][29][30] Primary biliary cirrhosis is an autoimmune liver disease that predominantly affects women and is characterized by chronic progressive destruction of small intrahepatic bile ducts with portal inflammation and subsequent fibrosis. The serological hallmark is the presence of antimitochondrial antibodies, which are found in 95% of patients.…”
Section: Overview Of Liver Alterationsmentioning
confidence: 99%
See 2 more Smart Citations